2020
DOI: 10.1007/s11214-020-00647-0
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Electricity at the Ice Giants

Abstract: Lightning was detected by Voyager 2 at Uranus and Neptune, and weaker electrical processes also occur throughout planetary atmospheres from galactic cosmic ray (GCR) ionisation. Lightning is an indicator of convection, whereas electrical processes away from storms modulate cloud formation and chemistry, particularly if there is little insolation to drive other mechanisms. The ice giants appear to be unique in the Solar System in that they are distant enough from the Sun for GCR-related mechanisms to be signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 94 publications
(158 reference statements)
0
14
0
Order By: Relevance
“…Intense convective storms large enough to be observed from Earth are frequent in Jupiter [37] and rare in Saturn [22,38]. In both planets, radio emissions emitted from lightning have been observed by different spacecraft [39], and lightning flashes have been observed in some of the most intense storms [40,41], including Jupiter locations with no evident storms in the observed cloud field [42,43], but lightning in Uranus and Neptune has only been inferred from radio signals [44][45][46].…”
Section: Observations Of Convective Activity In Uranus and Neptunementioning
confidence: 99%
“…Intense convective storms large enough to be observed from Earth are frequent in Jupiter [37] and rare in Saturn [22,38]. In both planets, radio emissions emitted from lightning have been observed by different spacecraft [39], and lightning flashes have been observed in some of the most intense storms [40,41], including Jupiter locations with no evident storms in the observed cloud field [42,43], but lightning in Uranus and Neptune has only been inferred from radio signals [44][45][46].…”
Section: Observations Of Convective Activity In Uranus and Neptunementioning
confidence: 99%
“…Our knowledge of ice giant atmospheres was reviewed shortly after the Voyager encounters by Lunine [29], and constraints on planetary origins from atmospheric composition and structure were reviewed by Mousis et al [30]. These reviews have been recently updated: Hueso & Sanchez-Lavega [31] review atmospheric dynamics and winds; Fletcher et al [32] review ice giant banding and global circulation; and Aplin et al [33] review measurements of atmospheric electricity on Uranus and Neptune. Ice giant atmospheres featured prominently on the first day of the discussion meeting, and new insights are revealed in this special issue: Hueso et al explore convective motions in hydrogen-rich atmospheres; Moses et al review the chemistry at work on the ice giants; and Melin et al and Moore et al describe the properties of the upper atmospheres and ionospheres.…”
Section: Science Themes For Future Explorationmentioning
confidence: 99%
“…While extraterrestrial lightning has been observed at Jupiter, Saturn, Uranus, and Neptune (Aplin et al., 2020), its existence at Venus remains an open question. Lorenz (2018) reviewed claims of detections and nondetections of lightning at Venus, concluding that while some type of electromagnetic activity is present (Russell et al., 2008), its properties are different from terrestrial lightning.…”
Section: Introductionmentioning
confidence: 99%
“…At radio frequencies, lightning produces strong, transient broadband emissions commonly known as "sferics" (Smith et al, 2002). Terrestrial sferics typically exhibit a f −2 power spectrum at frequencies below a few MHz, steepening to f −4 at higher frequencies (Levine & Meneghini, 1978).While extraterrestrial lightning has been observed at Jupiter, Saturn, Uranus, and Neptune (Aplin et al, 2020), its existence at Venus remains an open question. Lorenz (2018) reviewed claims of detections and nondetections of lightning at Venus, concluding that while some type of electromagnetic activity is present (Russell et al, 2008), its properties are different from terrestrial lightning.…”
mentioning
confidence: 99%